Seroprevalence of Toxoplasmosis (By Detecting IgM Antibodies) in Women with Repeated Abortions (Medical Forum Monthly, 2024)
Objective: To determine seroprevalence of Toxoplasmosis in women with repeated abortions in our local population.Study Design: Prospective Cross- sectional studyPlace and Duration of Study: This study was conducted in the Department of Microbiology Basic Medical Sciences Institute (BMSI) Jinnah Postgraduate Medical Centre (JPMC) Karachi from April 2006 to May 2008.Materials and Methods: Sera from 130 pregnant and post-aborted women with history of repeated abortions (group A) and 50 pregnant women with no history of abortion (group B – as controls ) were analyzed for Toxoplasma IgM antibodies by ELISA technique to see the prevalence of toxoplasmosis.Results: 24% of women of group A and 14% of women of group B were seropositive for Toxoplasma IgM antibodies. Most of the cases with toxoplasmosis have had their abortions in the first trimester. Gradual increase in Toxoplasma antibody positivity with increasing gravida was observed.Conclusion: Women with negative serological status are at risk of acquiring a primary infection during pregnancy, hence education regarding preventive measures should be provided to them and every pregnant woman may be advised for Toxoplasma IgM antibodies investigation.